Recent trends of Arabic language teaching methods in contemporary education environment (Journal Of Educational and Psychological Researches, 2015)
Arabic language the timeless language of the Qur'an ((I made it read Arabic you may understand)) (Al-Zukhruf No 3). It is a way to express his thoughts and feelings and capable of giving constant absorbed the needs of the times and meet the General requirements and interactive needs of life to achieve social and intellectual aspects.    The aim of current research to identify what teaching the contemporary trends in teaching, what the nature of knowledge and teaching methods, how do you rate the modern Arabic language teaching methods, the criteria for evaluating the effectiveness of teaching where the researcher has reached some recommendations: 1. establish the basics of environmental education to the students ' motivation to study environment and attention and promote awareness and understanding of all the obvious environmental knowledge, values, attitudes and skills needed to protect and improve the environment, maintain and acquire the skills needed to identify environmental problems and provide appropriate solutions.                                                  -Creation of students for tomorrow's world by stimulating students to understand the nature, characteristics and handling information and training on technology and embrace change in the patterns of professions and jobs, and public opinion of the students support and supports information and applications both on an individual level or at the level of educational institutions to speed up the overall development of society.                                               Realization of self-learning search to discover information and facts for themselves and how to learn from books or from the diverse experiences of teaching traditional modern and especially the ability to deal with a computer and the Internet and modern technology                                                                    4-acquire knowledge and facts and scientific concepts of functional here the focus is on imparting knowledge and facts associated with the knowledge of the skills, values and attitudes that will enable them to deal with the flow of knowledge, thus giving students a culture of information enabling them to coexist in the information society is a society of the future